Increased Incidences of Depression and Anxiety among Young People (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2025)
The article deals with the problem of increasing cases of depression and anxiety among young people aged 18-25 years. The relevance of the study is due to the increase in mental disorders, especially in the context of the COVID-19 pandemic, social changes and economic difficulties. The aim of the work was to determine the level of depression and anxiety among young people and identify factors contributing to their increase. The study methods included a cross-sectional survey of 200 participants using the Beck Depression Inventory (BDI) and Hamilton Anxiety Scale (HAM-A). Results showed that 45% of participants had high levels of depression and 50% had high levels of anxiety. Social isolation and financial difficulties were identified as significant factors contributing to higher levels of mental disorders. The discussion of the results highlights the need to develop mental health support programs for youth. The article concludes with conclusions about the importance of further research to understand the causes and consequences of mental disorders among youth.